Innovative strategies in the library: study of users of the physical-virtual library - Valverde, Jorge Luis (2020)
The paper was carried out in the San Carlos Campus, to analyze the perspective that the university community has, regarding the needs of information, access and use of the physical-virtual library; this with the aim of being able to optimize the services and products of the library. The study is part of the mixed approach, quantitative and qualitative data are extracted, and it is descriptive. Some results of the study are the university community makes regular use of libraries, university libraries and public libraries are the most consulted, the most used tool to search for information is Internet, the consultation to the physical-virtual library is little, the main need for information is the search for information, followed by training in the American Psychological Association (APA) normalization, as well as training in accessing and using the University’s virtual library. On the other hand, it can be concluded that it is important for campus to support the processes of continuous improvement of the library in order to offer a quality education, academics are a vital target of libraries, because they stimulate and encourage access and use from the physical-virtual library, on the part of the students; It is transcendental that the university authorities carry out an administrative directive, where the training of academics is required, with respect to the access and use of the physical-virtual library, as well as their different information resources and tools for research.